Effect of Silane Application and Heat Treatment on the Bond Strength of Translucent Zirconia to Glass-Reinforced Core Composite Using Universal Resin Cement: An in vitro Study - Veparala, Jaswanth Raj; Sampathi, Naga Lakshmi Reddy; Reddy, N Upendra Natha; Moosani, Gopi Krishna; Yalamanchi, Anusha; Reddy, E Sujayeendra Natha (International Journal of Dental Materials, 2025)
Background: Zirconia crowns are gaining popularity due to their excellent optical properties, minimal preparation requirements, high strength, and biocompatibility. Yttria-stabilized tetragonal zirconia polycrystals (Y-TZP) are now widely used as alternatives to PFM crowns, implant abutments, and implants. However, achieving reliable bonding remains a significant challenge.Aim: To evaluate the effect of silane application, with and without subsequent heat treatment, on the shear bond strength of translucent zirconia to glass-reinforced core composite using universal resin cement.Materials and Methods: Thirty translucent zirconia blocks (12 mm × 12 mm × 3 mm) were CAD/CAM milled and fully sintered from UPCERA ST zirconia blanks. The specimens were divided into three groups based on surface pretreatment: non-surface treated group (NSTG), silanized group (SG), and silanized with subsequent heat-treated group (SHTG). Thirty composite resin cylinders (2 mm in diameter and 3 mm in height) were fabricated using polyethylene tubes and light-cured according to the manufacturer’s instructions. A universal resin cement was used to lute the composite cylinders to the zirconia blocks, followed by light curing as per the manufacturer’s guidelines. Each specimen was then embedded in polymethyl methacrylate (PMMA) resin using polyethylene molds. Shear bond strength was measured using a universal testing machine. Data were subjected to the Kruskal-Wallis test applied for overall comparisons and the Mann-Whitney U test for pairwise group comparisons. A p-value of